Optimalisasi Pengelolaan SDM UMKM Kuliner Melalui Implementasi Sistem Penjadwalan Kerja dan SOP Pada Ayam Goreng Pak Memed - Jefri, Jefri Bagus Saputra; Butar Butar, Septama Pamuncak Butar Butar; Purwatiningsih, Aris Puji Purwatiningsih; Febriana, Artha Febriana; Hertiana Ikasari (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector contribute significantly to the Indonesian economy, but still face obstacles in human resource management, particularly in terms of work scheduling and the absence of written Standard Operating Procedures (SOPs). This community service activity focuses on optimizing HR management at Pak Memed's Fried Chicken MSME through the implementation of a structured shift work scheduling system and the development of systematic operational SOPs. The implementation method uses the Waterfall model, which includes Planning, Modeling, Implementation, Testing, and Evaluation. This approach allows the management system implementation process to run in a gradual, measurable, and participatory manner with partners. The results of the activity show an increase in employee understanding and ability to implement work schedules and SOPs, which has an impact on increasing operational efficiency, work discipline, and reducing turnover rates. In addition, the implementation of this management system strengthens the internal work structure, facilitates task distribution, and maintains consistent service quality. Recommendations for development include conducting regular evaluations and advanced training to ensure the continued implementation of SOPs and work systems. Overall, this activity has made a real contribution to the application of science and technology in improving the management of culinary MSME human resources, enabling businesses to develop more efficiently, productively, and competitively